Gestão de resíduos sólidos em uma propriedade rural - Cavalcante, Emília Mikaela das Chagas (Universidade Federal Rural do Semi-Árido, 2019)
This work analyzed the solid waste management in a rural property of Portalegre-RN aiming to develop a solid waste management system generated in the small property seeking to identify the waste produced and how it is stored and what is its final destination. The study had an exploratory-descriptive approach and the analysis was performed from January to June 2019, the solid waste generated on the property was identified and quantified for management purposes in their final destination and sizing of a system for waste reuse. The information obtained during the recognition period of the generated residues subsidized the elaboration of a PGRS waste management plan that foresees measures for the implementation of a composting system, biodigester, solid waste packaging in a more appropriate way, seeking the best way to make its disposal. discard, as a form of protection and preservation for the environment and the well-being of the population inserted in this environment.
Keywords: Zona rural; Resíduos agricolas; Gestão ambiental; Destinação; Armazenamento; Rural area; Agricultural waste; Destination; Environmental management; Storage; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA